2020
DOI: 10.1007/s13243-020-00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Vision guided robotic inspection for parts in manufacturing and remanufacturing industry

Abstract: Environmental and commercial drivers are leading to a circular economy, where systems and components are routinely recycled or remanufactured. Unlike traditional manufacturing, where components typically have a high degree of tolerance, components in the remanufacturing process may have seen decades of wear, resulting in a wider variation of geometries. This makes it difficult to translate existing automation techniques to perform Non-Destructive Testing (NDT) for such components autonomously. The challenge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Research reported in [52] investigated creation of an automation cell for an aircraft fan-blade repair with the integration of a 6-DoF industrial robot with an end-effector grinder and a computer vision system. Another study reported the use of vision-guided robotic technology for ultrasonic inspection of components in returned products [53].…”
Section: Sensors and Machine Vision For Inspectionmentioning
confidence: 99%
“…Research reported in [52] investigated creation of an automation cell for an aircraft fan-blade repair with the integration of a 6-DoF industrial robot with an end-effector grinder and a computer vision system. Another study reported the use of vision-guided robotic technology for ultrasonic inspection of components in returned products [53].…”
Section: Sensors and Machine Vision For Inspectionmentioning
confidence: 99%
“…Previous works have obtained good automated 3D reconstructions of parts by moving a robot-manipulated 3D scanner around a given component through a predefined path, along which multiple views of the scene are collected. In [26], the authors proposed using a robot arm to move a non-contact passive 3D scanning system, following spiral paths lying on paraboloid primitives and stopping at regular intervals with the camera pointing at the centre of the paraboloid, to collect photogrammetric views of relatively small industrial parts. Although this may be an acceptable scanning path for some objects, it can cause some portions of the part to not be scanned at all, some other areas to not be scanned to a satisfactory or acceptable extent and/or, on the contrary, some remaining areas to be over-sampled.…”
Section: Related Workmentioning
confidence: 99%
“…The merged point clouds create the complete 3D model. This whole process, going from the single range map to the whole model, is usually known as the 3D scanning pipeline [24,25]. Complete 3D reconstruction of a scene is typically achieved by establishing a relative motion between the scanning system and the object to reconstruct, while data is captured by the system.…”
Section: Related Workmentioning
confidence: 99%